A patient with Parkinson’s disease whose sleep status improved after the introduction of continuous subcutaneous foslevodopa/foscarbidopa infusion - Hirotaka Sakuramoto; Hiroaki Fujita; Keitaro Ogaki; Keisuke Suzuki (Clinical Parkinsonism & Related Disorders)
Continuous subcutaneous infusion of foslevodopa/foscarbidopa (LDP/CDP) may be effective in improving daytime symptoms in patients with Parkinson’s disease (PD). We report on a PD patient for whom LDP/CDP treatment improved motor symptoms, sleep disturbances and sleep architecture as measured by the mobile two-channel electroencephalography/electrooculography recording system.